CoAP Monitoring System Using Logical Grouping Technique - Yun Kang, Jeong; Silva, Nathali; Han, Kijun (International Journal of Engineering and Technology, 2018)
Most of IoT devices will have constraints in terms of memory add power. IETF proposed light-weight base Constrained Application Protocol (CoAP) at the application level. It supports two important features, observe and group communication. However, these two features are unable to work at the same time. In this paper, we propose a CoAP grouping technique using a gateway. Gateway generates device groups with resource type and saves groups’ information in Database. It helps perform operations on the observed results and user can easily manage system.
Keywords: Internet of Things; CoAP; Constraind device; Wireless Sensor Network (WSN); Machine to Machine (M2M)